A multimodal analysis of family representation in lifebuoy online advertisements - Intan Ananda Rahayu; Iwa Lukmana; Riesky Riesky (Passage, 2020)
Communication can be done not only through spoken or written language, but also visual texts. The use of visual and verbal modes is commonly found in advertisements. The purpose of this study is to investigate the visual and verbal representation of family in Lifebuoy online advertisements and the signification of the representation. This study employs a qualitative approach supported by simple descriptive quantification. The data for this study are several Lifebuoy online advertisements uploaded from 2012 to 2015 that are taken from https://www.facebook.com/lifebuoy/. The analysis focuses on the visual and verbal representation of family in the advertisements. In order to identify the visual representation, this study uses visual grammar as proposed by Kress and van Leeuwen (2006). The verbal representation is examined by using transitivity system as proposed by Halliday (1994). The findings show that family is represented as an active and affectionate group of people who are caring and willing to take care of each other.Keywords: Family representation, multimodal discourse analysis, online advertisements